2008
DOI: 10.1159/000136902
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and Electroglottographic Voice Characteristics in Chronic Cough and Paradoxical Vocal Fold Movement

Abstract: Objective: Chronic cough (CC) and paradoxical vocal fold movement (PVFM) may be associated with voice problems. Objective acoustic and electroglottographic (EGG) measures have the capacity to delineate these vocal characteristics. This study investigated acoustic and EGG voice features of CC and PVFM. Patients and Methods: Acoustic and EGG findings were compared among 5 groups of participants. The first 3 groups, CC (n = 56), PVFM (n = 8) and combined CC-PVFM (n = 55), included individuals with cough and respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 50 publications
0
6
0
2
Order By: Relevance
“…5 A study of acoustic and electroglottography (EGG) examinations also confirmed significant abnormalities in voice features in PVFMD patients as reduced HNR and increased jitter was determined in participants with PVFMD in comparison with healthy controls. 7 About aerodynamic measurements of voice (MPT and s/z ratio), we found MPT to be significantly longer in control subjects than PVFMD patients. We expected to measure an abnormal s/z ratio, as s/z ratio indicates poor laryngeal function, unfortunately we discovered it to be nearly equal between patients and control subjects.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…5 A study of acoustic and electroglottography (EGG) examinations also confirmed significant abnormalities in voice features in PVFMD patients as reduced HNR and increased jitter was determined in participants with PVFMD in comparison with healthy controls. 7 About aerodynamic measurements of voice (MPT and s/z ratio), we found MPT to be significantly longer in control subjects than PVFMD patients. We expected to measure an abnormal s/z ratio, as s/z ratio indicates poor laryngeal function, unfortunately we discovered it to be nearly equal between patients and control subjects.…”
Section: Discussionmentioning
confidence: 63%
“…4 However, abnormalities in acoustic and electroglottographic voice characteristics including reduced MPTs, greater jitter, reduced harmonics-to-noise ratio (HNR), reduced phonation range, and shorter closed phase of vocal fold vibration were established in PVFMD patients in comparison with healthy controls. [5][6][7] The objective of the present study was to compare quantitative acoustic parameters (jitter, shimmer, and HNR), as well as aerodynamic measurements (MPT, s/z ratio), perceptual evaluations of voice, and laryngostroboscopic findings of larynx between a group of asymptomatic PVFMD patients and healthy individuals. To our knowledge, this is the first such investigation focusing on both objective and subjective voice evaluations within the same patient group.…”
Section: Introductionmentioning
confidence: 99%
“…Although laryngoscopic methods are well established as fundamental in PVFM diagnosis, attempts to pinpoint voice quality impairments associated with the disorder have been pursued, using perceptual and objective methods [25,26]. Evidence of abnormalities associated with PVFM include reduced maximum phonation time (MPT), phonation range, and maximum phonation time (MPTs) as well as elevated perturbation measures (i.e., jitter and shimmer) in comparison with healthy controls [26][27][28].…”
Section: Evaluation Of Pvfmmentioning
confidence: 99%
“…Evidence of abnormalities associated with PVFM include reduced maximum phonation time (MPT), phonation range, and maximum phonation time (MPTs) as well as elevated perturbation measures (i.e., jitter and shimmer) in comparison with healthy controls [26][27][28]. Deterioration in voice quality in association with PVFM can be detected even between acute episodes [25,29].…”
Section: Evaluation Of Pvfmmentioning
confidence: 99%
“…Várias interpretações têm sido relatadas em relação às medidas da onda eletroglotográfica e seus parâmetros em diferentes padrões vocais com e sem alteração laríngea [23][24][25][26] . Dessa forma, optouse neste estudo pela utilização da avaliação eletroglotográfica em mulheres para investigar a função vocal, pois devido à configuração glótica, o sexo feminino apresenta alta prevalência de fechamento incompleto das pregas vocais quando comparado ao sexo masculino [23][24][25] mesmo em vozes não patológicas. Além disso, percebe-se que o nódulo vocal é mais frequente em mu lheres na faixa etária dos 30 aos 40 anos de idade 27,28 .…”
Section: Introductionunclassified